Stable fitness during COVID-19: Results of serial testing in a cohort of youth with heart disease - Powell, Adam W.; Mays, Wayne A.; Wittekind, Samuel G.; Chin, Clifford; Knecht, Sandra K.; Lang, Sean M.; Opotowsky, Alexander R. (Frontiers in Pediatrics, 2023)
Background: Little is known about how sport and school restrictions early during the novel coronavirus 2019 (COVID-19) pandemic impacted exercise performance and body composition in youth with heart disease (HD). Methods: A retrospective chart review was performed on all patients with HD who had serial exercise testing and body composition via bioimpedance analysis performed within 12 months before and during the COVID-19 pandemic. Formal activity restriction was noted as present or absent. Analysis was performed with a paired t-test. Results: There were 33 patients (mean age 15.3±3.4 years; 46% male) with serial testing completed (18 electrophysiologic diagnosis, 15 congenital HD). There was an increase in skeletal muscle mass (SMM) (24.1±9.2 to 25.9±9.1 kg, p<0.0001), weight (58.7±21.5 to 63.9±22 kg, p<0.0001), and body fat percentage (22.7±9.4 to 24.7±10.4%, p=0.04). The results were similar when stratified by age <18 years old (n=27) or by sex (male 16, female 17), consistent with typical pubertal changes in this predominantly adolescent population. Absolute peak VO2 increased, but this was due to somatic growth and aging as evidenced by no change in % of predicted peak VO2. There remained no difference in predicted peak VO2 when excluding patients with pre-existing activity restrictions (n=12). Review of similar serial testing in 65 patients in the 3 years before the pandemic demonstrated equivalent findings. Conclusions: The COVID-19 pandemic and related lifestyle changes do not appear to have had substantial negative impacts on aerobic fitness or body composition in children and young adults with HD.